First Contemporary Muslim Philosophers Conference (American Journal of Islam and Society, 1998)
Early Saturday morning on 16 May 1998, fifty people made their wayinto the conference room of Georgetown University’s SalaamIntercultural Center for the first annual conference of the Association ofContemporary Muslim Philosophers. Looking into their eyes, one couldsee a glimmer of hope and the fire of enthusiasm. Clearly, this was notgoing to be a run of the mill encounter of Muslim minds. Some of thegreatest intellects of the Muslim world were present, among themProfessor Seyyed Hossein Nasr, Dr. Taha B Jabir al ‘Alwani, and Dr. KamalHassan. Young students with fresh countenances and effervescent commentswaited to deliberate upon such issues as the difference betweenpublic and private philosophy, the role of postmodernism in the Muslimworld, and why and in what condition does the Muslim intellectual traditionfind itself.Ironically, this occurred in view of an immense Jesuit Crucifix heraldedby the Greek letters alpha and omega, which symbolize Christ.While for some this signified the contradiction and turmoil presentwithin current Muslim philosophical discourse, for others it embodieda promising message. For those who saw it as a positive symbol,including myself, the cross served to illustrate the universe, markingthe four cardinal directions of space, and the surrounding alpha andomega symbolized the all-encompassing nature of the Qur’an. On aterrestrial level, it verified the resilient nature of the Muslim intellectfor, quite obviously, we were a group of Muslims meeting in a Jesuitinstitution to talk about reviving Islamic philosophy. Nevertheless, theuniversal significance of that symbol was realized by the spirit of thegathering and in the profound discussions afforded by all those present.The conference started with a moment of reflection upon the versesof the Qur’an found in Surat al ‘Alaq: ...